(untitled) (Global Journal of Science Frontier Research, 2022)
This objective of this paper is to analyze and describe the way in which the effects of disciplinary power that crosses the pedagogical evaluation of mathematics textbooks constitute a list of knowledge that feeds back this productive field. In this search, we take Michel Foucault’s analysis of power as a parameter, more specifically the theories about disciplinary power. Inspired by the cartographic process, we produced the data from semi-structured interviews with former members of the National Textbook Program (PNLD), as well as with an editor who works in a large publishing group today. Data analysis allows us to describe the pedagogical evaluation of the PNLD as an important instrument for analysis, writing and validation of knowledge that is intended to be propagated, configuring itself in an examination of textbooks. .